EXPOSURE TO GOAT BILE FOR 28-DAYS CAUSES HEPATOCYTE INJURY: A HISTOPATHOLOGICAL STUDY - Rizki Isnantono Prabowo; Nurina Hasanatuludhhiyah; Nily Sulistyorini; Kusuma Eko Purwantari (Majalah Biomorfologi, 2022)
Highlights: 1. Bile consumption, especially goat bile, is believed to have therapeutic effects even though it contains harmful ingredients that can cause toxic effects on the liver2. The administration of goat bile for 28 days had a toxic effect on the liver of the mice based on histopathological findings Abstract: Background: Bile consumption by Indonesians is believed to have therapeutic effects, especially goat bile. Goat bile is thought to contain harmful ingredients that can cause toxic effects on the liver. However, the 28-days oral toxicity study of goat bile has not been performed. Objective: To analyze the hepatotoxic effect of subchronic administration of goat bile on the liver of mice (Mus musculus). Material and Method: This was an experimental research with a post-test-only control group design. The samples used were 32 Balb/C mice (Mus musculus), which were grouped into 4 groups. The samples were administered with goat bile orally (3.2, 6.4, or 12.8 mL/kg/day) for 28 days. The liver was taken for histopathological examination and the hepatocytes injury score was performed. The scoring results were analyzed using Kruskal-Wallis, Mann-Whitney, and Spearman correlation tests (p<0.05). Result: Goat bile administration was associated with hepatocyte injury (p= 0.004). Groups with goat bile administration of 6.4 and 12.8 mL/kg/day had significant differences with the control group (p= .015 and .029 respectively) and the 3.2 mL/kg/day administered group (p= 0.006 and 0.009 respectively). Moreover, the increased administration of goat bile had a positive correlation with the level of hepatocyte injury (p= 0.004 and r_s= 0.504) Conclusion: Goat bile administration for 28 days had a significant toxic effect on the liver of mice at a dose of 6.4 mL/kg/day.